X-rays from accretion shocks in classical T Tauri stars: 2D MHD modeling and the role of local absorption. Issue Volume 9:Issue S302(2013) (7th August 2014) - Argiroffi, C.; Bonito, R.; Orlando, S.; Miceli, M.; Reale, F.; Peres, G.; Matsakos, T.; Sthelé, C.; Ibgui, L.
Abstract: In classical T Tauri stars (CTTS) strong shocks are formed where the accretion funnel impacts with the denser stellar chromosphere. Although current models of accretion provide a plausible global picture of this process, some fundamental aspects are still unclear: the observed X-ray luminosity in accretion shocks is order of magnitudes lower than predicted; the observed density and temperature structures of the hot post-shock region are puzzling and still unexplained by models. To address these issues we performed 2D MHD simulations describing an accretion stream impacting onto the chromosphere of a CTTS, exploring different configurations and strengths of the magnetic field. From the model results we then synthesized the X-ray emission emerging from the hot post-shock, taking into account the local absorption due to the pre-shock stream and surrounding atmosphere. We find that the different configurations and strengths of the magnetic field profoundly affect the hot post-shock properties. Moreover the emerging X-ray emission strongly depends also on the viewing angle under which accretion is observed. Some of the explored configuration are able to reproduce the observed features of X-ray spectra of CTTS.